507 Late-Breaking: Heat Stress and Mitoq Supplementation Impact Skeletal Muscle Mitochondrial Capacities in Pigs. (8th October 2021) - Wesolowski, Lauren T; Guy, Chloey P; Mayorga, Edith J; Rudolph, Tori E; Freestone, Alyssa D; Rhoads, Robert P; Baumgard, Lance H; Selsby, Joshua T; White-Springer, Sarah H
Abstract: Heat stress can negatively impact pig health and performance but the effects of heat stress on skeletal muscle mitochondrial function are largely unknown. We hypothesized that mitochondrial function and capacity would be impaired in heat stressed (HS) compared to thermoneutral (TN) pigs but mitochondrially-targeted coenzyme Q (MitoQ) supplementation would rescue the impairment. Oxidative portions of the semitendinosus muscle were evaluated from TN and HS gilts receiving no supplementation (CON) or MitoQ for 2 d prior to and during the 24h environmental heat treatment (n = 8 per group). Mitochondrial oxidative phosphorylation (P) and electron transfer (E) capacities were determined via high resolution respirometry and mitochondrial volume density and function were quantified by citrate synthase (CS) and cytochrome c oxidase activities, respectively. Data were analyzed using linear models in SAS v9.4 with fixed effects of heat, MitoQ treatment (trt), and heat×trt interaction. There were trends for the interaction of trt and heat (P≤0.1) on integrative (per mg tissue) and intrinsic (relative to CS) P with complexes I and II (PCI+II ), maximum noncoupled E (ECI+II ), and E with complex II only (ECII ), in which all measures were greater in HS-MitoQ than TN-MitoQ (P≤0.03), but measures did not differ due to HS in CON pigs. The contribution of leak to total E (flux control ratio, FCRLeak ) was lesser in HS-MitoQ than HS-CON, TN-CON, and TN-MitoQ (P≤0.02). The FCRPCI was greater (P≤0.05) while the FCRPCI+II was lesser (P=0.01) in TN compared to HS pigs. Finally, the FCRPCI+II was greater (P=0.02) while the FCRECII tended to be lesser (P=0.09) for CON than MitoQ pigs. Neither mitochondrial volume density nor function were affected by HS or MitoQ supplementation. In total, these data indicate improved mitochondrial capacities following heat stress in pigs receiving MitoQ but no difference in mitochondrial capacities in unsupplemented, HS pigs.